2013
DOI: 10.1242/jcs.121988
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 is deactivated at integrin activation sites via an IQGAP1/filamin-A/RacGAP1 pathway

Abstract: SummaryCell migration makes a fundamental contribution to both normal physiology and disease pathogenesis. Integrin engagement with extracellular ligands spatially controls, via the cyclical activation and deactivation of the small GTPase Rac1, the dynamic membrane protrusion and cytoskeletal reorganization events that are required for directional migration. Although the pathways that control integrinmediated Rac1 activation are reasonably well defined, the mechanisms that are responsible for switching off act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 88 publications
3
76
0
Order By: Relevance
“…It has been demonstrated that active integrins, after initially activating Rac1 probably through a GEF (Guanine nucleotide Exchange Factor), subsequently recruit a complex involving a GAP (GTPase-activating protein) which down-regulates Rac1 activity in order to limit protrusive activity during cell migration [60,72]. Accordingly to these and also more recent findings [73], our data demonstrate that Rab7a depletion determines the accumulation of active β1-integrins at the leading edge of migrating cells (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been demonstrated that active integrins, after initially activating Rac1 probably through a GEF (Guanine nucleotide Exchange Factor), subsequently recruit a complex involving a GAP (GTPase-activating protein) which down-regulates Rac1 activity in order to limit protrusive activity during cell migration [60,72]. Accordingly to these and also more recent findings [73], our data demonstrate that Rab7a depletion determines the accumulation of active β1-integrins at the leading edge of migrating cells (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Formation of filopodia is mediated by active Rac1 that controls actin cytoskeleton rearrangements and integrins, cell surface receptors involved in adhesion, spreading and migration, are transported to filopodia tips by myosin X, an unconventional myosin [45,60]. Interestingly, we established that Rab7a depletion strongly reduces formation of filopodia (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Recent evidence clearly shows that, several integrin signals modulate the activity of Rho family GTPases through IQGAP1 (Wickstrom et al, 2010;Jacquemet et al, 2013aJacquemet et al, , 2013b, indicating IQGAP1 as a critical scaffold for signaling from transmembrane receptors.…”
Section: Control Of Iqgap Activitymentioning
confidence: 99%
“…This resulted in the recruitment of IQGAP1 to the tips of pseudopods. The RacGAP1-IQGAP1 complex restricts Rac activity [146,147], and this permits RhoA activation as well as the formation of cellular protrusions and the invasion of 3D matrices [146].…”
Section: P53 Gof Mutants Promote Cancer Cell Invasion By Altering Intmentioning
confidence: 99%